2022
DOI: 10.3390/nu14204368
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Aging and Neuroprotective Properties of Grifola frondosa and Hericium erinaceus Extracts

Abstract: Nutrition has relevant consequences for human health and increasing pieces of evidence indicate that medicinal mushrooms have several beneficial effects. One of the main issues in Western countries is represented by the challenges of aging and age-related diseases, such as neurodegenerative disorders. Among these, Parkinson’s disease (PD) affects 10 million people worldwide and is associated with α-synuclein misfolding, also found in other pathologies collectively called synucleinopathies. Here, we show that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 78 publications
0
22
0
Order By: Relevance
“…These improvements were related to the antioxidant properties of G. frondosa, as evidenced by the increase in the activity of antioxidant enzymes and total antioxidant capacity, and by the decrease in NO and MDA levels in old rat brain. The neuroprotective and anti-age potential of polysaccharides from G. frondosa has been also tested in the yeast cells and Drosophila melanogaster models of PD, showing the ability to reduce both ROS levels and the toxicity of synuclein [196].…”
Section: Pleurotus Ostreatusmentioning
confidence: 99%
“…These improvements were related to the antioxidant properties of G. frondosa, as evidenced by the increase in the activity of antioxidant enzymes and total antioxidant capacity, and by the decrease in NO and MDA levels in old rat brain. The neuroprotective and anti-age potential of polysaccharides from G. frondosa has been also tested in the yeast cells and Drosophila melanogaster models of PD, showing the ability to reduce both ROS levels and the toxicity of synuclein [196].…”
Section: Pleurotus Ostreatusmentioning
confidence: 99%
“…Moreover, some neurological disorders are accompanied by α-synuclein (α-syn) misfolding, and reports suggested that fungal extracts known to reduce α-syn toxicity through diverse processes, such as the reduction of protein aggregation, a decrease of the ROS level, and α-syn membrane delocalization supporting their anti-aggregation properties. Hence the reduction of protein aggregates can be a better approach to managing neurological disorders [42]. Therefore, BACE is considered a prime target for delaying amyloid pathology and managing AD [3,57,58].…”
Section: Bace Complexmentioning
confidence: 99%
“…Earlier reports explored the therapeutic roles and mechanism of action of polyphenols against age-related neurological disorders [39,40]. The plants Grifola frondosa and Hericium erinaceus are excellent sources of β-glucans and have better anti-aging properties, whereas polyphenols of extra virgin olive oil (oleuropein aglycone and hydroxytyrosol) synergistically modulate autophagy against neurodegeneration due to their strong antioxidant and anti-inflammatory properties [40][41][42]. Nature provides an abundant resource of bioactive metabolites, which could be safe and economical to produce novel inhibitors of critical regulatory enzymes for the management of metabolic disorders, including neurological diseases [29,43,44].…”
Section: Introductionmentioning
confidence: 99%
“…7 Grifola frondosa is a type of large medicinal and edible fungi, rich in polyphenols, sterols, proteins, polysaccharides and other active substances, and has many effects such as hypoglycemia, antitumor, anti-virus, anti-oxidantion and so on. 8,9 Previous reports have confirmed that G. frondosa has different degrees of inhibition on HIV virus, influenza virus and herpes simplex virus type I. 10 Therefore, G. frondosa is an important resource for the development of nutritional and functional foods with antiviral activity.…”
Section: Introductionmentioning
confidence: 97%